Sonographic Predictors of Antepartum Bleeding in Placenta Previa - Smith, Devin D.; Adesomo, Adebayo A.; Gonzalez-Brown, Veronica M.; Russo, Jessica; Shellhaas, Cynthia; Costanstine, Maged M.; Frey, Heather A. (American Journal of Perinatology, 2024)
Objective To evaluate the association between sonographic features of placenta previa and vaginal bleeding (VB).Study Design Retrospective cohort study of women with placenta previa identified on ultrasound between 160/7 and 276/7 weeks gestation. Placental distance past the cervical os (DPO), placental thickness, edge angle, and cervical length (CL) were measured. The primary outcome was any VB and the secondary outcome was VB requiring delivery. Median values of the sonographic features were compared for each of the outcomes using the Mann–Whitney U test. Receiver operating characteristic curves were used to compare the predictive value of sonographic variables markers and to determine optimal cut points for each measurement. Logistic regression was used to estimate the association between each measure and the outcomes while controlling for confounders.Results Of 149 women with placenta previa, 37% had VB and 15% had VB requiring delivery. Women with VB requiring delivery had significantly more episodes of VB than those who did not require delivery for VB (1.5, interquartile range [IQR] [1–3] vs 1.0 [1–5]; p = 0.001). In univariate analysis, women with VB had decreased CL (3.9 vs. 4.2 cm; p < 0.01) compared with those without. Women with VB requiring delivery had increased DPO (2.6 cm IQR [1.7–3.3] vs. 1.5 cm [1.1–2.4], p = 0.01) compared with those without. After adjusting for confounders, only CL < 4 cm remained independently associated with increased risk of VB (adjusted odds ratio: 2.27, 95% confidence interval [1.12–4.58], p = 0.01). None of the measures were predictive of either outcome (area under the curve < 0.65).Conclusion Decreased CL may be associated with risk of VB in placenta previa.Key Points
Keywords: placenta previa; vaginal bleeding; distance past the os; sonographic markers